Studi Kasus Pemilihan Slice Thickness Pada Protokol Pemeriksaan CT Scan Sinus Paranasaldengan Klinis Sinusitis di Instalasi Radiologi Dr. Soedono Madiun - Kusuka, Arrizal Nazaro; Mukmin, Amril; Mufida, Widya (Innovative: Journal Of Social Science Research, 2025)
The examination of the CT Scan of the Paranasal Sinuses with clinical sinusitis at the Radiology Installation of Dr. Soedono Madiun Hospital uses a slice thickness reformat of 0.6 mm and a maximum of 3 mm with head CT scanning with the paranasal sinus CT protocol in order to obtain slice thickness slices below 1 mm and using windo bone. The selection of the use of slice thikness 0.6 and the use of windowing bone according to the Operational Procedure (SOP). Meanwhile, according to Bruce W. Long, (2016), the CT-Scan examination of the paranasal sinuses a slice thickness of 3-5 mm.The type of research is qualitative descriptive with a case study approach to study how the procedure for CT Scan scan of the paranasal sinus in patients with indications of sinusitis at the Radiology Installation of dr. Soedono Madiun Hospital, the research was carried out in November 2024 - April 2025, with 3 radiographers and 1 specialist doctor. Data collection techniques by observation, interviews and documentation studies. Data analysis is carried out by data collection, data reduction, data presentation and then conclusions are drawn. Based on the observation results of the reason for the use of a slice thickness of 0.6 mm in the CT scan examination of the paranasal sinus with clinical sinusitis, the use of a slice thikness of 0.6 mm is in accordance with the request of the sending doctor and approved by the radiologist specialist. The use of a 0.6 mm slice thikness produces a radiographic image that has noise, but can show a more detailed anatomy of the paranasal sinuses. The selection of windowing used in CT Scan examination with clinical sinusitis uses window bone which can show the entirety of the anatomy of the facial bone cavity and can evaluate the bone structure in the sinuses whether they are infected or not. Based on this research can be concluded that the use of a 0.6 mm slice thikness on a CT scan of the paranasal sinus with clinical sinusitis can reveal a more detailed and optimal anatomy of the paranasal sinuses, thus easily helping the radiologist to establish the diagnosis appropriately. The selection of windowing is also important in conducting anatomical assessments, the bone window is used to see or display the bone structures around the paranasal sinuses in high detail, for example such as the sinus wall, nasal septum, and osteomeatal complex.